2016
DOI: 10.1123/jsm.2015-0347
|View full text |Cite
|
Sign up to set email alerts
|

No More “Good” Intentions: Purchase Behaviors in Sponsorship

Abstract: The growth of sport sponsorship has led to an increase in the number of studies measuring sponsorship outcomes in different sport settings. Most studies, however, have focused on understanding the factors leading to purchase intentions. A more accurate assessment of sponsorship effectiveness would come through measuring actual purchase behaviors. The purpose of this study was to examine a sport sponsorship model that included awareness, fit, attitude toward the sponsor, past purchases, purchase intentions, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 0 publications
0
16
0
3
Order By: Relevance
“…Our study focused on just one specific sponsor, as in other published studies (e.g. Walraven et al 2014, Zaharia et al 2016. Therefore, our conclusions should not be extended to the whole world of basketball nor to any other sports.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Our study focused on just one specific sponsor, as in other published studies (e.g. Walraven et al 2014, Zaharia et al 2016. Therefore, our conclusions should not be extended to the whole world of basketball nor to any other sports.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, returns may be negative if, for example, doping scandals appear during the partnership, as the research of Drivdal et al (2018) into professional cycling showed. Additionally, Zaharia et al (2016) found that, although the vast majority of participants in their study recognized Samsung as the sponsor of the English Premier League football team, Chelsea F.C., none of the remaining intermediate variables considered (attitudes and purchase intentions) had an influence on the real sales of the brand.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…A investigação sobre patrocínio desportivo globalmente tem concentrado a atenção nos resultados afetivos e comportamentais dos espectadores (Eddy & Cork, 2019;Ko & Kim, 2014). Contudo, para além dessas respostas, também a notoriedade da marca, enquanto resultado cognitivo (e.g., Biscaia et al, 2013;Biscaia et al, 2014;Biscaia & Rocha, 2018;Eagleman & Krohn, 2012;Hickman, 2015;Lough et al, 2014;Rogic et al, 2019;Silva, 2016;Walsh et al, 2008;Zaharia et al, 2016), tem começado a suscitar a atenção, embora num reduzido número de estudos na perspetiva baseada no desportoparticipação (Eddy & Cork, 2019).…”
Section: Revisão De Literaturaunclassified
“…Embora nem sempre na perspetiva do desporto-participação (Eddy & Cork, 2019), uma quantidade significativa de pesquisas tem seguido a orientação para avaliação da notoriedade do patrocínio (e.g., Biscaia et al, 2013;Biscaia et al, 2014;Biscaia & Rocha, 2018;Hickman, 2015;Rogic et al, 2019;Silva, 2016;Walsh et al, 2008;Zaharia et al, 2016), incluindo no contexto das corridas de atletismo (Beaton et al, 2011;Eagleman & Krohn, 2012;Eddy & Cork, 2019;Lough et al, 2014), mas nenhuma avaliou a dependência entre a taxa de reconhecimento da marca do patrocinador e as marcas locais e internacionais. No desporto-participação os corredores realizam a prática da corrida porque estão envolvidos com essa atividade.…”
Section: Reconhecimento Das Marcas Patrocinadorasunclassified